Solid–Liquid Host–Guest Composites: The Marriage of Porous Solids and Functional Liquids. Issue 52 (8th October 2021) - Sheng, Zhizhi; Ding, Yi; Li, Guangyong; Fu, Chen; Hou, Yinglai; Lyu, Jing; Zhang, Kun; Zhang, Xuetong
Abstract: Composite materials can provide remarkable improvements over the individual constituents. Especially, with a liquid component introduced into a solid porous host, solid–liquid host–guest composites have recently come to the forefront with exceptional functions that promise them for a wealth of applications. Combining the unprecedented dynamic, transparent, omniphobic, self‐healing, diffusive and adaptive nature of functional liquid with inherent solid host's property, solid–liquid host–guest composites can realize the ease of fabrication, long‐term stability, and a broad spectrum of enhanced properties, which cannot be fully met by conventional solid–solid composites or liquid–liquid composites. This review presents the state‐of‐the‐art progress in solid–liquid host–guest composites. Initially, the concept, classification, design strategy, as well as fabrication methods as a path forward to develop the composites are unraveled, and further it is elaborated on how the functionality of porous solid and functional liquid can be harnessed to create composites with a broad range of unique properties, especially, the optical, thermal, electric, mechanical, sorption, and separation properties. With these fascinating properties, a myriad of emerging applications such as optical devices, thermal management, electromagnetic‐interference shielding, soft electronics, gas capture and release, and multiphase separations are touched upon, inspiring more frontier researches in materials science, interfacial chemistry, membrane science, engineering, and multidisciplinary. Finally, this review provides the perspective on the future directions of solid–liquid host–guest composites and assesses the challenges and opportunities ahead. Abstract : Solid–liquid host–guest composites have featured the ease of fabrication, long‐term stability, and a broad spectrum of unprecedented properties, which cannot be fully met by conventional solid–solid composites or liquid–liquid composites. They have greatly evolved in a myriad of emerging applications. With new concepts in mind and persistent efforts, new functions and applications of the solid–liquid host–guest composites will appear.